Wheat gluten hydrolysate affects race performance in the triathlon - Koikawa, N.; Aoki, E.; Suzuki, Y.; Sakuraba, K.; Nagaoka, I.; Aoki, K.; Shimmura, Y.; Sawaki, K. (Biomecical Reports, 2013)
Wheat gluten hydrolysate (WGH) is a food ingredient, prepared by partial enzymatic digestion of wheat gluten, which has been reported to suppress exercise-induced elevation of serum creatinine kinase (CK) activity. However, its effects on athletic performance have not yet been elucidated. This is the presentation of an experiment performed on five female college triathletes who completed an Olympic distance triathlon with or without ingestion of 21 g of WGH during the cycling leg. The experiment was performed in a crossover double-blind manner. The race time of the running leg and thus the total race time was significantly shorter when WGH was ingested. However, serum CK levels exhibited no apparent differences between the two WGH or placebo groups